Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The role of the hidden curriculum in enhancing intellectual security in Saudi education from the point of view of students of the third secondary students and the reasons for its weakness from the point of view of teachers Mrs. Nouf Atallah Al-Enezi , Mrs. Sarah Mohammed Al-Rashidi , Mrs. Ataf Lahiq Al-Anzi 2. The effect of the using Prior & Acquired Knowledge Strategy on Achievement in Science and Reflective Thinking among Seventh Graders in UNRWA School Mrs. Eman Ahmad Ayesh 3. Trends of middle school students in Al-Ahsa Governorate in the use of simulation technology in education Mr. Ahmed Sami Al-Nasser , Prof. Ahmed Abdullah Al-Dariwish 4. The Impact of the Implementation of Comprehensive Quality Assurance Standards on Achieving Modern Global Trends in Teaching Science to Public Secondary School Students in Khartoum Dr. Taghreed Mohamed Osman Mahmoud Yousif 5. The Degree of Mathematics Teachers’ Use of Electronic Assessment Tools in the Primary Stage from their Perspective and Educational Supervisors’ Perspective in Makkah region Mr. Hani Talal Ayesh Al-Lahyani 6. Psychological happiness among workers and volunteers at the COVID-19 Vaccine Center in Taif Governorate Asst-Prof. Jaza Obeid Alosaimi, Co-Prof. Asmaa Abdulaziz Al-Hussein 7. Evidence-Based Practices for early childhood teachers for deaf and hard of hearing According to the Council for Exceptional Children Standards (CEC) Mrs. Nouf Ali Alghamdi , Dr. Mazen Abdulrahman Alghamdi 8. The Quality of Work Life and the Relationship Motivation for Achievement of Faculty Members Hail University in the Kingdom of Saudi Arabia Asst-Prof. Jaza Obeid Alosaimi , Asst-Prof. Ayesha Alnemah Alaghdaf